Descriptions of three new species of Dicopomorpha Ogloblin (Hymenoptera: Chalcidoidea: Mymaridae) from India, with one new country record and a revised key to Indian species - Athithya, Ayyavu; Manickavasagam, Sagadai (Zootaxa, 2023)
Three new species of Dicopomorpha Ogloblin (Hymenoptera: Mymaridae), D. lathae Manickavasagam and Athithya sp. n., D. manickavasagami Athithya sp. n., and D. mohani Manickavasagam and Athithya sp. n., are described from Karnataka, Tamil Nadu and Kerala, Manipur and Assam states, respectively. Dicopomorpha koreana Triapitsyn and Berezovskiy is reported for the first time from India and a revised key to all 10 Indian species of the genus is provided.